Political and Moral Aspects of Guaranteeing the Principles of International Law - ZADOROZHNA, Svitlana (European Journal of Law and Public Administration, 2018)
International legal practice once again proves a leading role in regulating international relations, it is a political and moral component. In analyzing the basic principles of international law from the point of view of the mechanism for their implementation, one should proceed from the degree of absolute social and moral value to both the state separately, and for the entire international community as a whole. The subjects of the international community must realize their rights and responsibilities only within the limits that do not affect international peace and security, the basic principles of humanity and cooperation of states in vital areas of global coexistence. Modern positivists believe that the state assumes international legal obligations on its own accord (will), but then these obligations remain valid regardless of the consent of the state, due to the principle of good faith. The above-mentioned thoughts indicate rather that states are inclined to comply with international obligations that are in line with their public interests, while the general principles of international law are, first and foremost, a universally accepted interest of the global community. One of the elements of the moral and ethical mechanism for the implementation of the general principles of international law is international politeness. International courtesy (comitas gentium) - a set of rules of benevolence, correctness, restraint and mutual respect of participants in international communication, which are not legally binding. Only a holistic, coherent mechanism of legal, political and moral-ethical implementation of the implementation of the general principles of international law at the national, supranational and international levels can guarantee the realization of the goals and objectives of all humanity in the form of general principles of international law.
Keywords: the principles of international law, the moral aspect of guaranteeing the principles of international law, the political mechanism of guaranty of the principles of international law, international politeness, the comitas gentium, the good faith in international law.